Simulating the impact of methadone prescribing and pharmacy dispensing on opioid treatment and overdose in New York State: A study protocol for an agent-based modeling study - Noa Krawczyk; Megan Miller; Ignacio Bórquez; Caroline Rutherford; Georgiy Bobashev; Pamela Mund; Katherine Keyes; Magdalena Cerdá; Ashly E. Jordan (PLoS ONE, 2025)
Amid the ongoing overdose crisis, U.S. lawmakers are considering policy reforms that could significantly change availability and accessibility of methadone treatment (MT) for opioid use disorder (OUD). However, uncertainty remains about which potential changes will lead to the greatest health benefits while minimizing unintended harms. In this protocol, we describe a planned NIH-funded study (R21DA061660) to simulate alternative MT delivery scenarios currently being considered in U.S. policy discussions, and estimate their impact on population-level rates of treatment initiation and retention and opioid overdose across different sociodemographic groups. We will use an agent-based model focused on 16 counties in NY State to simulate two alternative policy scenarios compared to the current status quo of opioid-treatment program (OTP) delivered MT: 1) office-based prescribing by addiction-certified providers with pharmacy and OTP dispensing; and 2) office-based prescribing by general practitioners with pharmacy and OTP dispensing. Agents will represent individuals with OUD and we will simulate access to MT based on alternative policy scenarios (e.g., locations of existing OTPs vs. provider offices and pharmacies). Probabilities of treatment initiation, retention, and opioid overdose will be informed by estimates from the scientific literature and administrative datasets from NY State. Multiple implementation scenarios will be considered to account for potential variation in adoption of office-based methadone by patients, providers, and pharmacies. To ensure relevance to directly impacted communities and policy makers, the study involves a collaboration between academic researchers and NY State government partners and relies on input from an Expert Advisory Board of people with lived and living experience with methadone, addiction medicine, and policy experts. Findings will be disseminated via a public dashboard. This study will inform ongoing policy discussions and shed light on the potential of researcher-policy partnerships to promote evidence-based policies that can reduce overdose and improve population health.